(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: World Health Organization (WHO) and United Nations Children’s Fund (UNICEF) “Exclusive breastfeeding (EBF)” is explained as “the infant receives only breast milk, no other liquids or solids. Its recommended for the first 6 months of life, and then complementary feeding should be started. EBF helps to reduce child morbidity and mortality from several diseases such as diarrhea, respiratory and / or ear infections and other infectious diseases, shielding lactation women from breast and ovarian cancer. In addition to offers societal economic and environmental benefits, The objective of this study was to assess the knowledge and awareness of exclusive breast feeding among mothers with a child < 2 years of age. Method: A descriptive cross-sectional study was carried out in Health Directorate of Holy Karbala city. The study consist of (487) mothers how attendant to six Primary Health Care center (PHC). The collected data was done by direct interview with mothers and using a questionnaire form that designed based on the study objectives according to WHO criteria. Data were analyzed by SPSS “ Statistical Package for the Social Sciences”, the descriptive statistics included numbers (N) and percentage (%), and the inferential statistical test was done by using Chi-Square test (?2), P-value (Probability of chance ) was equal or less than 0.05 considered as statistically significant to find for any association between the results variables. Result: A total of 487 participants were included in the study and the rate of response was 92.7%. The highest percentage (66.3%) of study sample were full in the age group (21-30) years, and more than three quarters were lived in urban area. Nearly half of the study sample 47% had primary education and 60% those housewives, and the main source of information being family and friends (84.4%). As an overall assessment, 61.8% of the study sample had good knowledge and awareness about exclusive breastfeeding, with highly significant differences to education level ,occupation residence of the mother. Conclusion: Over half of the subjects had good knowledge and awareness of exclusive Breastfeeding. And, on the other hand, there was a very significant difference between education level, occupation and mother’s residence with a level of knowledge.